2023
DOI: 10.1371/journal.pone.0286289
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy among women planning for pregnancy, pregnant or breastfeeding mothers in Jordan: A cross-sectional study

Abstract: Background Women planning to become pregnant, who are pregnant, and who are breastfeeding are more hesitant to take COVID-19 vaccines compared to other women globally. Aim This study investigates COVID-19 vaccine hesitancy among women, who are planning for pregnancy, currently pregnant, and breastfeeding women in Jordan Methods An online cross-sectional study was conducted in the biggest three cities in Jordan, including 874 women. Results Women who were planning for pregnancy, pregnant, or breastfeeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In this study, 57 out of 304 participants with a previous history of COVID-19, 21 reported a history of COVID-19 infection as a reason for refusal. In line with our findings, another study conducted by Masa’deh et.al in Jordan showed that women who had previously been infected with COVID-19 reported higher hesitancy levels than those who hadn’t ( 20 ). Also, some healthcare providers and obstetricians-gynecologists are not setting a good example by getting vaccinated.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 57 out of 304 participants with a previous history of COVID-19, 21 reported a history of COVID-19 infection as a reason for refusal. In line with our findings, another study conducted by Masa’deh et.al in Jordan showed that women who had previously been infected with COVID-19 reported higher hesitancy levels than those who hadn’t ( 20 ). Also, some healthcare providers and obstetricians-gynecologists are not setting a good example by getting vaccinated.…”
Section: Discussionsupporting
confidence: 92%